Rare bird documentation form for Tundra Swan at Princeton Marsh, 1991 - Barker, Ann M.et al (1991)
Rare bird documentation form for two Tundra Swans at Princeton Marsh in Scott County, IA on December 19, 1991. Epson - sheet feed